FAVORABLE CLINICAL COURSE OF POSTTHROMBOTIC SYNDROME - THE INDICATOR OF THE EFFECTIVENESS OF TREATMENT OF DEEP VEIN THROMBOSIS - D.R. RADZHABOV; D.D. SULTANOV; F.M. MAKHMADALIZODA (Avicenna Tajik State Medical University, 2019)
Objective: Evaluation of the effectiveness of conservative treatment of patients in the acute period of deep vein thrombosis (DVT) by exploring the course of the postthrombotic syndrome (PTS) in the short and long term observation. Methods: Analyzed the results of the examination and treatment of 105 patients with DVT of lower limbs between the period of 2015 and 2018. Patients were divided into two groups. The first (main) group included 40 patients who were treated under the new treatment regimen developed by us. In this group, patients were examined and treated inpatient by an angiosurgeon in the conditions of the Vascular Surgery Department. The second (control) group included 65 patients who received treatment in outpatient settings or other prevention facilities without the involvement of a specialist. Results: In the main group, there was persistent hypocoagulation within the acceptable level, there was a decrease in swelling and tension of the limb, decreased pain syndrome, eliminated secondary spasm of peripheral arteries. In addition, earlier (up to 3 months) signs of rechanneling of the bloodplated segments of the deep veins of the lower limbs were observed in this group. By the end of the second year, recanalization of varying degrees was in 86.4% (against 61% in the control group), which contributed to the easier flow of PTS. In many ways, it was the degree of recanalization that determined the severity of the PTD. In the control group in the acute period of DVT did not receive treatment at all - 13 patients, outpatient treatment in different specialists were 27, the remaining 25 were treated in the non-specialized hospital of other divisions. The therapy that was given by patients of the control group without proper control of the clotting system of blood and subsequently without rehabilitation measures can be regarded as not optimal management of patients. The examination conducted in the long term with the initial treatment of a vascular surgeon showed worse results compared to the main group. Thus, 39% of patients retained occlusion of the thrombosed venous segment, that was significantly above the average. This fact indicates that this group has seen a slowdown in the rechanneling of the deep veins of the lower limbs, apparently due to the inefficiency of the obtained acute treatment, which contributed to the more severe current of PTS. Conclusion: The favorable and relatively mild clinical course of PTS was observed in the main group, whereas the control group was dominated by patients with severe currents. At the same time, occlusive forms were observed in 39% of patients in the control and in 13.6% of patients in the main group.